IMPROVING STUDENTS’ TOEIC SCORE THROUGH COOPERATIVE LEARNING - Retnaningsih, Nanik Sri; Sarosa, Teguh (Jurnal Inovasi Pendidikan, 2010)
The purposes of this research are: (1) to find out whether or not Cooperative Learning methods improve students' English proficiency to score higher in TOEIC; (2) to know the students' interest toward the TOEIC class; and (3) to describe the students' activity during the TOEIC class. The method used in this research is a classroom action research done collaboratively with the English teacher, conducted in two cycles from August 28th until October 28th 2010 at the twelfth grade of SMK Negeri 1 Wonogiri by applying Think-Pair-Share (TPS) and Student Team Achievement Division (STAD) methods. Data were collected through observation, questionnaire, and test. The data were analyzed by using FLINT system, Comprehensive and Individual Analysis, and mean statistical formula. Result shows that students' TOEIC score improves. It is also found that students became more interested in TOEIC class. Students' activity also improves. It can be concluded that Cooperative Learning can (1) improve students' TOEIC score, (2) attract the students to join TOEIC class, and (3) push the students to actively participate in the class.